2021
DOI: 10.1097/ee9.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Environmental hazards, social inequality, and fetal loss: Implications of live-birth bias for estimation of disparities in birth outcomes

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…[17][18][19] Goin et al demonstrated an underestimation of preterm birth when only live births are considered, suggesting our findings may be attenuated. 18 It is well known that apart from complications at the time of birth, untreated STIs also increase the risk of transmission directly to the baby during birth, predisposing the child to potential longterm complications. 20 We would have also liked to examine additional maternal outcomes which were not available in the data.…”
Section: Limitations Of the Datamentioning
confidence: 59%
“…[17][18][19] Goin et al demonstrated an underestimation of preterm birth when only live births are considered, suggesting our findings may be attenuated. 18 It is well known that apart from complications at the time of birth, untreated STIs also increase the risk of transmission directly to the baby during birth, predisposing the child to potential longterm complications. 20 We would have also liked to examine additional maternal outcomes which were not available in the data.…”
Section: Limitations Of the Datamentioning
confidence: 59%
“…Similarly, another form of collider stratification bias, resulting from the necessity of conditioning ASD assessments on live births, could induce a falsely protective association of smoking among preterm cohorts, given that tobacco smoke exposure in pregnancy is a risk factor for both premature birth and fetal loss (Liew et al, 2015;Pineles et al, 2014). The bias can occur if exposed children who are born preterm and do not survive were otherwise at a higher risk for ASD than those who did survive, potentially leading to a paradoxical protective association with smoking if it preferentially leads to fetal loss among fetuses susceptible to ASD (Goin et al, 2021), as described previously for air pollution (Leung et al, 2021;Raz et al, 2018). However, a key question with regard to 'live-birth bias' is whether the interest lies in all conceptions or just among live births who reach the age when a diagnosis is possible, in which case, such bias is less likely or may be entirely moot.…”
Section: Discussionmentioning
confidence: 99%
“…However, residential mobility and time–activity patterns during pregnancy were likely nondifferential conditional on the covariates included, with the magnitude of the bias being contingent on the degree of misclassification in our sample. Furthermore, our analyses were restricted to live-born children and so our estimates may be biased upward ( Goin et al. 2021 ; Leung et al.…”
Section: Discussionmentioning
confidence: 99%